The Construction of Inheritance Law Reform in Indonesia: Questioning the Transfer of Properties through Wasiat Wājibah to Non-Muslim Heirs - Zubair, Asni; Latif, Hamzah; Hariyanto, Al Furqon Dono (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This article examines the construction of inheritance law reform in the transfer of properties through wasiat wājibah to non-Muslim heirs. Questioning the jurisprudence of the Supreme Court which makes wasiat wājibah  as an alternative in giving inheritance rights to heirs who are prevented from getting an inheritance due to religious differences (non-Muslims). This study is an empirical legal study that examines the decisions of the Supreme Court relating to the transfer of inheritance to non-Muslims. The study concludes that in terms of inheritance law reform is an alternative in changing Islamic law that must be carried out in response to changes in community social conditions. The construction of inheritance law reform in judicial decisions has formulated inheritance law by giving inheritance rights to heirs of different religions (non-Muslims) by means of wasiat wājibah . The jurisprudence of the Supreme Court of the Republic of Indonesia has expanded Article 209 of the Compilation of Islamic Law by adding parties who can receive a wasiat wājibah, including heirs who are prevented from inheriting due to religious differences. The construction of inheritance law reform on the transfer of inheritance properties with wasiat wājibah  in the jurisprudence of the Supreme Court of the Republic of Indonesia has exceeded the quantitative limit in granting wasiat wājibah. The impression does not pay attention to the signs in the application of wasiat wājibah  by ignoring the maximum limit. Wasiat wājibah  as a solution is not unacceptable as inheritance law reform but must still guide the legal media used by considering the basic rules that surround it.